Performance Improvement for Detecting Brain Function Using fNIRS: A Multi-Distance Probe Configuration With PPL Method - Chen, Xinrui; Song, Xizi; Chen, Long; An, Xingwei; Ming, Dong (Frontiers in Human Neuroscience, 2020)
To improve the spatial resolution of imaging and get more effective brain function information, a multi-distance probe configuration with three kinds of distance (28.2mm, 40mm and 44.7mm) and 52 channels is designed. At the same time, a data conversion method of modiﬁed Beer-Lambert law (MBLL) with partial path length (PPL) is proposed. In the experiment, three kinds of task, grip of left hand (LG), grip of right hand (RG) and rest (RE), is performed with eight healthy subjects. First, with a typical single-distance probe configuration (30 mm, 24 channels), the feasibility of the proposed MBLL with PPL is preliminarily validated. Further, the characteristic of the proposed method is evaluated with the multi-distance probe configuration. Compared with MBLL with differential path length factor (DPF), the proposed MBLL with PPL is able to acquire more obvious concentration change and can achieve higher classification accuracy of the three tasks. Then, with the proposed method, the performance of the multi-distance probe configuration is discussed. Results show that, compared to a single distance, the joint of the three distances has better spatial resolution and could explore more accurate brain activation information. Besides, the classification accuracy, of the three tasks, obtained with the combination of three distances is higher than that of any combination of two distances. Also, with the joint of the three kinds distance, the 2-class classification between different tasks is carried out. Both theory and experimental results demonstrate that, using multi-distance probe configuration and the MBLL with PPL method, the performance of brain function detecting by NIRS can be improved.